β-amyloid infusion into lateral ventricle alters behavioral thermoregulation and attenuates acquired heat tolerance in rats - Matsuzaki, Kentaro (Temperature (Austin), 2015)
We investigated behavioral thermoregulatory function and acquired heat tolerance of β-amyloid (Aβ)-infused rats. Male Wistar rats were anesthetized and implanted in the intraperitoneal cavity with a temperature transmitter. Aβ peptide (4.9–5.5 nmol) was dissolved in a solvent of 35% acetonitrile and 0.1% trifluoroacetic acid (pH 2.0). The solvent was used as the vehicle. An osmotic pump contained 234 ± 13.9 μl of Aβ solution was subcutaneously implanted in the back and was cannulated into the left cerebral ventricle. Moreover, 0.5 µg of AlCl(3) was injected into the right cerebral ventricle with a micro syringe pump (Aβ-infused rats). The solvent-infused rats were used as control rats (CN rats). After 2 weeks, rats were placed in a thermal gradient and their intra-abdominal temperature (T(ab)) and their ambient temperatures (T(a)) selected (T(s)) were measured for 3 consecutive days. In an additional study, rats were kept at a T(a) of 32°C for 4 weeks to attain heat acclimation. Then, rats were subjected to a heat tolerance test, i.e. they were exposed to a T(a) of 36°C for 160 min. Although there were clear day-night variations of T(s) and T(ab) in CN rats, patterns were significantly abolished in Aβ-infused rats. Moreover, heat tolerance obtained by heat acclimation was attenuated in Aβ-infused rats. These results suggest that Aβ-infusion in the lateral ventricle modifies behavioral thermoregulation and lowers an ability to acclimate to heat in rats.